An insight into the bioelectrochemical photoreduction of CO2 to value-added chemicals - Priyanka Gupta; Mohammad Tabish Noori; Abraham Esteve Núñez; Nishith Verma (iScience, 2021)
Summary: Goal of sustainable carbon neutral economy can be achieved by designing an efficient CO2 reduction system to generate biofuels, in particular, by mimicking the mechanism of natural photosynthesis using semiconducting nanomaterials interfaced with electroactive bacteria (EAB) in a photosynthetic microbial electrosynthesis (PMES) system. This review paper presents an overview of the recent advancements in the biohybrid photoanode and photocathode materials. We discuss the reaction mechanism observed at photoanode and photocathode to enhance our understanding on the solar driven MES. We extend the discussion by showcasing the potential activity of EABs toward high selectivity and production rates for desirable products by manipulating their genomic sequence. Additionally, the critical challenges associated in scaling up the PMES system including the strategies for diminution of reactive oxygen species, low solubility of CO2 in the typical electrolytes, low selectivity of product species are presented along with the suggestions of alternative strategies to achieve economically viable generation of (bio)commodities.